Kaji Eksperimental Alat Pendingin Termoakustik Dengan Panjang Tabung Resonator λ/2 Dan λ/4 - Deviawan, Damar Agung; Agustina, Dinni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Thermoacoustic is a system that converets energy from high amplitude sound waves into heat energy which produces temperature differences or vice versa, each of which can be used for heat engines and heat pump. This combination of pressure and temperature oscillastion will cause a thermoacoustic phenomenon, acoustic power input provided by a loudspeaker (driver) in the form of high amplitude soundwaves. In this study using λ/2 and λ/4 resonator tubes with a length of 80 cm and 60 cm. For the position of the stack in this study that is at the position of the tip farthest end of the sound source or loudspeaker box (stack position 2), and the position of the stack at the closest end of the sound source or loudspeaker box (stack position 1). From the analysis results obtained temperature differences on both sides of the stack that is on stack position 1 resonator tube λ / 2 2.69 C, on stack position 2 resonator tubes λ / 2 2.81 C, while on stack position 1 tube λ / 4 4.14 C and stack position 2 resonator tubes λ / 4 5.15 C. stack position influences the occurrence of thermoacoustic phenomena, the better position is stack position 2 because the greatest amplitude occurs in the position farthest from the sound source. Keyword: Refrigeration, thermoacoustic, stack, resonator